PEMAHAMAN KONSEP MATEMATIS MAHASISWA MENGGUNAKAN BUKU TEKS DENGAN PENDEKATAN KONSTRUKTIVISME - Yunita, Alfi; Sovia, Anny; Hamdunah, Hamdunah (Jurnal Elemen, 2020)
Understanding mathematical concepts is an important ability to be mastered by students. It allows students to understand the essence of teaching and the material being learned. The purpose of the study is to analyze how mathematical concept understanding of students who learn by using constructivism-approach textbooks that have been developed in previous studies. This research was a descriptive study with a qualitative approach. The study was conducted by giving 10 item problems of conceptual understanding to participants that consisting of 17 students STKIP PGRI Sumatera Barat in Basic Mathematics subject. Furthermore, the students' answers were analyzed descriptively. The results of the study showed that a mastery achievement of the highest mathematical concept understanding was on indicators of using model, diagram, and symbols to represent a concept. While the lowest concept mastery was on indicators of recognizing conditions for determining a concept, students had difficulty in determining a settlement set from an inevitable inequality of absolute value.